(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2025)
Today’s seminar comes out of the concerns the organisers of this event have about the narrow framing of the current independent review of Community Learning & Development. For example, the overview of the review states: Community Learning and Development (CLD) is a professional practice within education with delivery stretching across all stages of lifelong learning…The purpose of CLD is to provide early intervention and prevention to those experiencing, or at risk of experiencing, inequality of opportunity within the education and skills system. (Scottish Government, No Date) As a result of this perceived narrowing of the scope of CLD work, four of us working on CLD programmes in Scottish universities wrote an open letter (Galloway et al, 2024) to express our concerns and invite support from the field of practice. Our concerns are summarised by this extract from the letter: We argue that the learning and development components of CLD cannot be separated without losing the ethos and values of the profession in relation to social justice. We also note that within the terms of reference, ‘educational’ refers explicitly to learning and skills for employment, neglecting longstanding broader social justice aims for lifelong, life wide education as recognised formally by the Scottish Government.